Fiscal Distress of Local Government Study on Regencies/Cities in the Provinces of East Nusa Tenggara, Maluku, and North Maluku - Halim, Abdul; Moi, Maria Odriana Veronica; Baswir, Revrisond (Jurnal Dinamika Akuntansi, 2016)
This study aims to examine the factors that influence the occurrence of fiscal distress in local government. The degree of decentralization, local financial dependency ratio and local financial independence ratio were used to predict fiscal distress. The method used in this study is a quantitative research and used the regencies/cities in the province of East Nusa Tenggara, Maluku and North Maluku were taken as samples. The results showed different result with previous studies, that the degree of decentralization, local financial dependency ratio and local financial independence ratio do not affect the fiscal distress.